Course in Evaluation and Management of Pharmaceutical Information for Clinical Pharmacy Graduate Students Based on Group Discussion: Evaluation of Improvement in Ability to Generate Pharmaceutical Information from Questionnaire Results - Matsuyama, Kenji; Otsuka, Makoto; Tagawa, Noriko; Otsuka, Kuniko; Kato, Fumie; Kamae, Isao; Yanagisawa, Shinichiro (Iryo Yakugaku (Japanese Journal of Pharmaceutical Health Care and Sciences), 2005)
Though the importance of pharmaceutical information in university pharmacist education has been widely recognized in recent years very few such curriculums have been initiated in continuing education courses for graduate pharmacists. A course in the evaluation and management of pharmaceutical information for clinical pharmacy graduate students was therefore started in 2000 at the Graduate School of Kobe Pharmaceutical University as a continuing education program for pharmacists in hospitals and pharmacies. In the course, students selected two pharmaceutical care-related themes and made presentations on them to the rest of their class using MS Power Point. The contents of the presentations were discussed afterwards in small groups. In order to evaluate the educational effect of this new form of study, a questionnaire survey was conducted from 2000 to 2001. Dividing attendees into pharmacists and full-time department graduate students as appropriate, and conducting tutorials for small groups, efficient training in problem solution capability was given. In addition, the creation of an educational website enabled EBM information to be collected quickly and accurately and this aided the training of the students in evaluating information. The active discussion of presentations in small groups enhanced the ability of students to generate quality information and the differences between before and after taking the course were shown statistically by the results of the questionnaire.